2019
DOI: 10.3389/fped.2019.00447
|View full text |Cite
|
Sign up to set email alerts
|

Part II. Comparison of Neurodevelopmental Outcomes Between Normothermic and Hypothermic Pediatric Cardiopulmonary Bypass

Abstract: Objectives: In the previous study we demonstrated that normothermic cardiopulmonary bypass (N-CPB, ≥35°C) provided better early clinical outcomes compared to mild/moderate hypothermic cardiopulmonary bypass (H-CPB, 28–34°C) for congenital heart surgery. In this follow-up study we compare early neurodevelopmental outcomes 2–3 years post-surgery.Methods: In this retrospective, non-randomized observational study, the medical notes of children from our previous cohort were reviewed after 2–3 years. Demographic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Poncelet et al ( 11 ) conducted research on postoperative neurological complications in 18 children, with an average of 4 years of follow-up, after excluding those with related genetic diseases and multiple malformation syndromes and performed late neurological and neuropsychological evaluations and found no significant difference in the verbal intelligence quotient (IQ) ( P = 0.296), operational IQ ( P = 0.144), and total score IQ ( P = 0.065). Hannon et al ( 25 ) also exhibited greater neurodevelopmental delay, language delay, motor delay, learning difficulties, behavioral disorders, neurological deficits, and growth delay after cardiac surgery in the hypothermia group than in the normal temperature group. However, consistent with the results of studies conducted in humans and animals, which have been interpreted as suppression of brain tissue metabolism under HCPB, the present study does not provide obvious evidence that NCPB is superior to HCPB in protecting brain tissues from damage.…”
Section: Discussionmentioning
confidence: 94%
“…Poncelet et al ( 11 ) conducted research on postoperative neurological complications in 18 children, with an average of 4 years of follow-up, after excluding those with related genetic diseases and multiple malformation syndromes and performed late neurological and neuropsychological evaluations and found no significant difference in the verbal intelligence quotient (IQ) ( P = 0.296), operational IQ ( P = 0.144), and total score IQ ( P = 0.065). Hannon et al ( 25 ) also exhibited greater neurodevelopmental delay, language delay, motor delay, learning difficulties, behavioral disorders, neurological deficits, and growth delay after cardiac surgery in the hypothermia group than in the normal temperature group. However, consistent with the results of studies conducted in humans and animals, which have been interpreted as suppression of brain tissue metabolism under HCPB, the present study does not provide obvious evidence that NCPB is superior to HCPB in protecting brain tissues from damage.…”
Section: Discussionmentioning
confidence: 94%
“…A large-animal study recently showed hypothermic CPB attenuated platelet degranulation and coagulopathy and better maintained oxygenator performance in swine ( 249 ). Several RCTs studying pediatric populations showed normothermic CPB as noninferior to hypothermic CPB with endpoints including inotrope duration, intubation time, hospital stay, and early neurodevelopmental outcomes in low-risk populations ( 250 , 251 ).…”
Section: Strategies To Modulate Cpb-associated Inflammatory Responsementioning
confidence: 99%